Manufacturing method of high strength titanium alloy using ferrochromium and high strength titanium alloy

Ferrochrome-based alloying with chromium, iron, and silicon in controlled amounts addresses the challenge of high-strength titanium alloys, achieving enhanced mechanical properties and cost-effectiveness by minimizing cracking and maintaining elongation rates.

JP2025502826AActive Publication Date: 2025-01-28KOREA INST OF MATERIALS SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024539776
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-29
Filing Date
2022-12-06
Publication Date
2025-01-28
Estimated Expiration
2042-12-06

AI Technical Summary

Technical Problem

Existing titanium alloys face challenges in achieving high strength and elongation rates while maintaining cost-effectiveness, as adding alloy elements to enhance strength often increases production costs and can lead to cracking or reduced elongation.

Method used

A method involving the use of ferrochrome as an alloy additive, comprising chromium, iron, silicon, and carbon, with controlled additions of less than 4% by weight, to produce high-strength titanium alloys through processes like vacuum dissolution and heat molding, ensuring stability and strength without excessive costs.

Benefits of technology

The method results in titanium alloys with tensile strengths of 861 to 1165 MPa and elongation rates of 2.2 to 16.8%, reducing production costs by using non-toxic elements and avoiding cracking, while maintaining mechanical integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502826000001_ABST
    Figure 2025502826000001_ABST
Patent Text Reader

Abstract

A method for producing a high-strength titanium alloy using ferrochromium and a high-strength titanium alloy are disclosed. The method for producing a high-strength titanium alloy according to the present invention includes the steps of adding ferrochromium containing Cr, Fe, Si, and C to pure Ti, melting and cooling the mixture to form a titanium alloy base material, and then hot forming the titanium alloy base material. At this time, the content of ferrochromium is less than 4 wt%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing high-strength titanium. More specifically, the present invention relates to a method for producing a high-strength titanium alloy using ferrochromium.

[0002] The present invention also relates to titanium alloys that can exhibit high strength along with good elongation. [Background technology]

[0003] Titanium has excellent specific strength, corrosion resistance and biocompatibility and is therefore widely used in a wide range of industrial fields such as aerospace, national defense, the energy industry, medicine and consumer goods.

[0004] Titanium alloys are generally classified into pure titanium, α alloys, α-β alloys, and β alloys based on their stability at room temperature. Among these, α alloys are known to have excellent creep strength and weldability, while β alloys have improved workability.

[0005] Pure titanium is cheaper than other titanium alloys in terms of cost, and has excellent formability, weldability, workability, and corrosion resistance. However, pure titanium has low strength and is limited in its application fields. Most fields in which titanium is used require high strength properties, and in this case, the addition of large amounts of alloy elements raises the risk of high costs.

[0006] Therefore, there is a need to develop titanium alloys made of relatively inexpensive elements that can control properties such as excellent strength, formability, weldability, workability, corrosion resistance, and biocompatibility while minimizing cost increases, and methods for manufacturing such alloys. Summary of the Invention [Problem to be solved by the invention]

[0007] The problem to be solved by the present invention is to provide a method for producing a high-strength titanium alloy using ferrochromium. In particular, the present invention provides a method for producing a high-strength titanium alloy using ferrochromium as an alloy additive, which not only reduces the production cost of the titanium alloy but also ensures strength and elongation.

[0008] Another problem to be solved by the present invention is to provide a titanium alloy having high strength together with a good elongation ratio.

[0009] The object of the present invention is not limited to the object mentioned above, and other objects and advantages of the present invention not mentioned above can be understood from the following description and can be more clearly understood from the embodiments of the present invention. In addition, it can be easily understood that the object and advantages of the present invention can be realized by the means and combinations thereof as set forth in the claims. [Means for solving the problem]

[0010] In order to solve the above problems, a method for manufacturing a high-strength titanium alloy according to an embodiment of the present invention includes the steps of: (a) adding ferrochromium, which contains chromium (Cr), iron (Fe), silicon (Si), and carbon (C), to pure titanium (Ti); (b) melting the result of step (a) and cooling it to form a titanium alloy base material; and (c) hot forming the titanium alloy base material, wherein the ferrochromium is added in an amount of less than 4 wt% based on the total weight of the titanium alloy.

[0011] A method for producing a high-strength titanium alloy according to a preferred embodiment of the present invention includes the steps of: (a) adding ferrochrome containing chromium (Cr), iron (Fe), silicon (Si), and carbon (C) to pure titanium (Ti); (b) melting the result of step (a) and cooling it to form a titanium alloy base material; and (c) hot forming the titanium alloy base material, wherein the ferrochrome contains 20-35 wt% iron (Fe), 1-4 wt% silicon (Si), and 0.15 wt% or less carbon (C), with the remainder being chromium (Cr) and unavoidable impurities, and the amount of the ferrochrome added is less than 4 wt% of the total weight of the titanium alloy. In this case, the titanium alloy produced may contain 0.1 to 3.0 weight % chromium (Cr), 0.1 to 1.0 weight % iron (Fe), 0.01 to 0.1 weight % silicon (Si), 0.4 weight % or less oxygen (O), with the remainder being titanium (Ti) and unavoidable impurities, and may have a tensile strength of 861 to 1165 MPa.

[0012] It is preferable that the ferrochromium be added in an amount of 0.5 to 2% by weight based on the total weight of the titanium alloy.

[0013] The hot forming can be carried out at a temperature of 800 to 850° C. with a forming rate of 90% or less.

[0014] In order to solve the above problems, a high-strength titanium alloy according to an embodiment of the present invention is characterized by containing 0.1-3.0 wt% chromium (Cr), 0.1-1.0 wt% iron (Fe), 0.01-0.1 wt% silicon (Si), 0.4 wt% or less oxygen (O), with the remainder being titanium (Ti) and unavoidable impurities.

[0015] A high-strength titanium alloy according to a preferred embodiment of the present invention contains 0.1-3.0 wt% chromium (Cr), 0.1-1.0 wt% iron (Fe), 0.01-0.1 wt% silicon (Si), and 0.4 wt% or less oxygen (O), with the chromium (Cr) content being greater than the iron (Fe) content, with the remainder being titanium (Ti) and unavoidable impurities, and is characterized by having a tensile strength of 861-1165 MPa.

[0016] The chromium content may be 1.7 to 4 times the iron content.

[0017] The titanium alloy may have a molybdenum equivalent ([Mo]eq.) of 5 or less, as represented by the following formula 1, and a β transformation point of 840 to 930°C ([] in formula 1 is the weight % of the component).

[0018] [Formula 1] [Mo]eq.=[Mo]+0.2[Ta]+0.28[Nb]+0.4[W]+0.67[V]+1.25[Cr]+1.25[Ni]+1.7[Mn]+1.7[Co]+2.5[Fe]

[0019] The titanium alloy may have a yield strength of 460 to 1280 MPa and a Young's modulus of 95 to 105 GPa. Effect of the Invention

[0020] According to the manufacturing method of the high strength titanium alloy of the present invention, low-carbon ferrochrome made of elements (Cr, Fe, Si, etc.) that are harmless to the human body is used as an additive alloy material for pure titanium (c). This not only reduces the cost of raw materials and the cost of the process, but also provides advantageous effects in terms of securing strength and elongation, compared to adding individual elements such as Cr, Fe, Si, etc.

[0021] The above-mentioned effects and specific effects of the present invention will be described in conjunction with the following description of the preferred embodiment of the invention. [Brief description of the drawings]

[0022] [Figure 1a] FIG. 1 shows the phase fraction of a pure titanium (Ti-0.05O) specimen. [Figure 1b] This is a diagram showing the phase fraction of a specimen in which 4 wt% of ferrochromium was added to pure titanium (Ti-0.05O). [Figure 1c]This is a diagram showing the phase fraction of a specimen in which 0.5 wt% of ferrochromium was added to pure titanium (Ti-0.05O). [Figure 2a] FIG. 1 shows the phase fraction of a pure titanium (Ti-0.39O) specimen. [Figure 2b] This is a diagram showing the phase fraction of a specimen in which 4 wt% of ferrochromium was added to pure titanium (Ti-0.39O). [Figure 2c] This is a diagram showing the phase fraction of a specimen in which 0.5 wt% of ferrochromium was added to pure titanium (Ti-0.39O). [Figure 3a] FIG. 1 is a diagram showing mechanical properties of specimens 1 and 3 of comparative examples and specimens 1 to 4 of examples. [Figure 3b] FIG. 1 is a diagram showing mechanical properties of specimens 2 and 4 of comparative examples and specimens 5 to 8 of examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] The above-mentioned objects, features and advantages will be described in detail below, so that those skilled in the art can easily implement the technical idea of ​​the present invention. In describing the present invention, if a detailed description of the known technology according to the present invention is considered to make the gist of the present invention unclear, the detailed description will be omitted. Hereinafter, a preferred embodiment of the present invention will be described in detail with reference to the accompanying drawings.

[0024] Hereinafter, a method for producing a high-strength titanium alloy using ferrochromium according to several embodiments of the present invention and the high-strength titanium alloy will be described.

[0025] There are two methods to increase the strength of pure titanium: adding alloy elements to increase the strength, and reducing the size of the internal crystal grains through plastic processing and heat treatment to increase the strength. However, these methods require the addition of an additional process to refine the crystal grains by adding alloy elements, which increases the cost. In addition, the method of refining the crystal grains through plastic processing and heat treatment has the disadvantage that the mechanical properties of the titanium alloy produced depending on the process change significantly, which may lead to a process that is difficult to directly apply to the actual production process.

[0026] Therefore, it can be said that the method of adding alloying elements is more advantageous than the method of refining crystal grains by plastic processing and heat treatment. In particular, it can be said that the most preferable method for minimizing cost increases and increasing strength is to select and alloy inexpensive alloying elements. Furthermore, in order to ensure biostability, it is preferable that toxic elements such as Co, Cu, Ni, and V are not added, and the titanium alloy according to the present invention does not contain these elements, and in exceptional cases, they are inevitably contained as impurities.

[0027] After extensive research, the inventors have developed a method of alloying pure titanium by adding ferrochrome, which contains Fe, Cr, and Si, which are non-toxic and easily soluble in pure titanium. In particular, Si, an element contained in ferrochrome, is expected to provide nucleation sites during melting and refine the crystal grains of the melted ingot. As a result, a new Ti-Cr-Fe-Si alloy based on pure titanium has been developed.

[0028] The manufacturing method of the high-strength titanium alloy using ferrochromium will be described in more detail below.

[0029] The method for producing a high-strength titanium alloy according to the present invention includes the steps of adding ferrochrome, which contains chromium (Cr), iron (Fe), silicon (Si), and carbon (C), to pure titanium (Ti), melting the pure titanium and ferrochrome and then cooling them to form a titanium alloy base material, and hot forming the titanium alloy base material.

[0030] The melting of pure titanium and ferrochrome can be performed by various known methods such as vacuum melting, electron beam melting, plasma arc melting, non-consumable electrode arc melting, and induction skull melting. Hot forming can be performed by hot rolling, hot forging, and the like. Hot forming can be performed at 800-850°C with a forming ratio of 90% or less. In the case of rolling, the forming ratio can be expressed as a reduction ratio. In the case of the present invention, as described below, less than 4 wt% of ferrochrome is added, and as a result, even when forming is performed at 800-850°C with a forming ratio of 90%, the effect of no cracks occurring can be provided.

[0031] After hot forming, various methods can be used for cooling, such as water cooling, air cooling, furnace cooling, etc. The cooling method can be determined according to whether or not there is a further hot process after hot forming, for example, if there is no further hot process, water cooling can be performed after hot forming. After hot forming, further heat treatments such as homogenization treatment, solution treatment, aging treatment, etc. can be performed.

[0032] One feature of ferrochrome melting is that the temperature required to melt ferrochrome is significantly lower than the temperature required to melt chromium, iron, silicon, etc. individually, and is similar to the melting point of titanium. This allows ferrochrome to be melted together with pure titanium at a relatively low temperature, thereby reducing the manufacturing cost of titanium alloys.

[0033] In the present invention, the amount of ferrochromium added is preferably less than 4% by weight based on the total weight of the titanium alloy. More preferably, it is 3% by weight or less, and most preferably, it is 0.5 to 2% by weight. The addition of ferrochromium can increase the strength compared to pure titanium. However, if the amount of ferrochromium added is 4% by weight or more, the elongation rate is very low and cracks may occur.

[0034] Ferrochrome may contain 20 to 35 weight percent iron (Fe), 1 to 4 weight percent silicon (Si), and 0.15 weight percent or less carbon (C), with the remainder being chromium (Cr) and unavoidable impurities. Ferrochrome is characterized in that the Cr content is higher than the Fe content. The Cr content in ferrochrome may be 1.7 to 4 times, for example, 2 to 4 times, the Fe content.

[0035] Chromium (Cr) is a non-toxic element and a higher β-phase stabilizing element than molybdenum (Mo) in titanium alloys. Adding chromium to pure titanium can increase its strength due to the solid solution strengthening effect. However, adding too much chromium increases the possibility of fracture during the forming process due to the formation of Laves Phase (TiCr2). For example, it is known that the addition of Cr to titanium alloys such as Ti-33Zr-3Fe-2Cr alloy, Ti-33Zr-5Fe-2Cr alloy, and Ti-33Zr-7Fe-2Cr alloy forms Laves phase, resulting in crack behavior (during compression testing).

[0036] Iron (Fe), like chromium (Cr), is non-toxic and is a beta-phase stabilizing element with a higher degree of stability than molybdenum. Adding iron to pure titanium can increase its strength due to the solid solution strengthening effect. However, when titanium alloys containing 2% or more by weight of iron are melted, macro- or micro-segregation can be induced, and when heat-treated at a certain temperature, a very weak phase, TiFe phase, can be formed.

[0037] Silicon (Si) is a non-toxic element that forms many nucleation sites when titanium alloys are melted, inducing fine grains. Silicon also contributes to increasing the static strength of titanium alloys. However, if the silicon content exceeds 0.25 wt%, it can promote cracking due to the formation of brittle silicide.

[0038] When the content of ferrochromium is less than 4% by weight, the above-mentioned preferred ranges of the contents of chromium, iron, and silicon in the titanium alloy can be satisfied.

[0039] The titanium alloy according to the present invention may contain oxygen (O) in an amount of 0.4% by weight or less based on the total weight of the titanium alloy. Oxygen is an interstitial element that does not significantly affect corrosion resistance and is a solid-solution strengthening alloying element that strengthens the lattice. However, if oxygen is contained in an amount exceeding 0.4% by weight, it can suppress twin deformation at low temperatures, thereby rapidly reducing impact resistance.

[0040] By the above-mentioned method, the present invention can provide a high-strength titanium alloy, which is characterized by containing 0.1-3.0% by weight of chromium (Cr), 0.1-1.0% by weight of iron (Fe), 0.01-0.1% by weight of silicon (Si), 0.4% by weight or less of oxygen (O), and the balance being titanium (Ti) and unavoidable impurities. The contents of Cr, Fe, and Si in the high-strength titanium alloy according to the present invention are determined by the amount of ferrochromium added, and the above-mentioned contents of Cr, Fe, and Si can be satisfied by adding an amount of ferrochromium of less than 4% by weight, more preferably 3.0% by weight or less, and most preferably 0.5-2.0% by weight.

[0041] The high-strength titanium alloy according to the present invention may have a molybdenum equivalent ([Mo]eq.) represented by the following formula 1 of 5 or less ([] in formula 1 is the weight % of the component).

[0042] [Formula 1] [Mo]eq.=[Mo]+0.2[Ta]+0.28[Nb]+0.4[W]+0.67[V]+1.25[Cr]+1.25[Ni]+1.7[Mn]+1.7[Co]+2.5[Fe]

[0043] The high-strength titanium alloy according to the present invention may have a β transformation point of 840 to 930°C.

[0044] Furthermore, experimental results show that the high-strength titanium alloy according to the present invention may have a tensile strength of 540 to 1370 MPa, and more preferably a tensile strength of 861 to 1165 MPa, a yield strength of 460 to 1280 MPa, and a Young's modulus of 95 to 105 GPa, taking into account the elongation rate in the following examples.

[0045] Working Example Hereinafter, the configuration and function of the present invention will be described in more detail with reference to preferred embodiments of the present invention. However, these are merely preferred examples of the present invention, and are not to be construed as limiting the present invention in any sense. Contents not described in the following embodiments can be fully inferred by those skilled in the art, and therefore the description thereof will be omitted.

[0046] 1. Analysis of Ferrochrome The three ferrochrome specimens were subjected to component analysis as follows. EDS analysis was performed three times for each of the three locations (left, center, and right) of each 10 mm x 10 mm specimen. The results are shown in Table 1.

[0047] [Table 1]

[0048] All three specimens contained about 66% by weight of Cr, about 31% by weight of Fe, and about 3% by weight of Si, and it was found that the difference in the content of the components was not large.

[0049] In the following, an experiment was carried out on ferrochrome specimen #1.

[0050] After removing the surface oxide layer from ferrochrome specimen #1, the contents of O, N, H, and C were analyzed by EDS. The results are shown in Table 2.

[0051] [Table 2]

[0052] Ferrochrome is classified into low carbon ferrochrome, medium carbon ferrochrome, and high carbon ferrochrome according to the carbon content, and among these, low carbon ferrochrome means that the carbon content is 0.2 weight % or less or 0.15 weight % or less. In the case of the ferrochrome specimen #1 analyzed above, the carbon content is about 0.1 weight % and the chromium content is about 67%, which corresponds to low carbon ferrochrome.

[0053] The melting points of Cr, Fe and Si are 1907°C, 1538°C and 1414°C, respectively, but it is known that the melting point of low-carbon ferrochrome, which has a carbon content of 0.15% by weight or less, is about 1620°C. In addition, the melting point of titanium is 1668°C.

[0054] O, N, C, H, etc. in titanium are the main elements that reduce fracture ductility and require special management. These elements in pure titanium must be controlled to the weight percent or less shown in Table 3 (there are very small differences in the allowable values ​​depending on the country). H in particular requires special management compared to other elements because even a small amount of it reduces fracture ductility.

[0055] [Table 3]

[0056] In the case of the ferrochrome specimen #1 analyzed above, it is a low carbon ferrochrome and satisfies the maximum weight percent or less for elements such as O, N, C, and H in Table 3.

[0057] Titanium alloy specimen manufacturing Pure titanium (Ti-0.05O and Ti-0.39O) and ferrochrome with the contents shown in Table 4 were melted in an induction skull melting furnace to form titanium alloys, which were then cooled to produce ingots with a width of 10 mm, a length of 30 mm, and a thickness of 10 mm.

[0058] The ingots were rolled at 830° C.±20° C. to a forming ratio of about 90% as shown in Table 4, and then water-cooled to prepare titanium alloy specimens according to Comparative Examples 1-2 and Examples 1-8.

[0059] Table 4 shows the Mo equivalent and β transformation point according to the ferrochromium content in the titanium alloy specimens manufactured according to Comparative Examples 1-2 and Examples 1-8. And Table 5 shows the Cr, Fe and Si contents according to the ferrochromium added in the titanium alloy specimens according to Examples 1-8.

[0060] [Table 4]

[0061] [Table 5] ※Cr:Fe:Si=66:31:3

[0062] Figure 1a shows the phase fraction of a pure titanium (Ti-0.05O) specimen according to Comparative Example 1. Figure 1b shows the phase fraction of a titanium alloy specimen manufactured by adding 4 wt% ferrochromium to pure titanium (Ti-0.05O). Figure 1c shows the phase fraction of a titanium alloy specimen manufactured by adding 0.5 wt% ferrochromium to pure titanium (Ti-0.05O).

[0063] The pure titanium (Ti-0.05O) used in FIGS. 1a to 1c corresponds to Grade 1 or Grade 2, which has an oxygen content of about 0.05% by weight.

[0064] Referring to Table 4 and FIG. 1a, it can be seen that pure titanium (Ti-0.05O) exists in the β phase at high temperatures of about 890° C. or higher, but actually exists only in the α phase at lower temperatures.

[0065] However, referring to Table 4 and Figure 1b, in the case of a titanium alloy specimen manufactured by adding 4 wt% ferrochromium, it exists in the β phase at high temperatures of about 850°C or higher, coexists in the β phase and the α phase at 600-850°C, and exists in the α phase at temperatures below about 600°C. In particular, referring to Figure 1b, it can be seen that TiCr2 precipitates in the 600-650°C range during the phase transformation from the high-temperature β phase to the low-temperature α phase. If there is too much TiCr2, there is a possibility that it may break during the forming process.

[0066] On the other hand, referring to FIG. 1c, in the case of the titanium alloy specimen manufactured by adding 0.5 wt.% of ferrochromium, unlike FIG. 1b, almost no precipitates are formed, which is more advantageous in the forming process.

[0067] Figure 2a shows the phase fraction of a pure titanium (Ti-0.39O) specimen according to Comparative Example 2. Figure 2b shows the phase fraction of a titanium alloy specimen manufactured by adding 4 wt% ferrochromium to pure titanium (Ti-0.39O). Figure 2c shows the phase fraction of a titanium alloy specimen manufactured by adding 0.5 wt% ferrochromium to pure titanium (Ti-0.39O).

[0068] The pure titanium (Ti-0.39O) used in Figures 2a to 2c can be said to correspond to Grade 4, which has an oxygen content of about 0.39% by weight.

[0069] Referring to Table 4 and FIG. 2a, it can be seen that pure titanium (Ti-0.39O) exists in the β phase at high temperatures of about 930° C. or higher, but actually exists only in the α phase at lower temperatures.

[0070] However, referring to Table 4 and Figure 2b, in the case of a titanium alloy specimen manufactured by adding 4 wt% ferrochromium, it is found that at high temperatures of about 910°C or higher, the β phase exists, the β phase and the α phase coexist at 600-910°C, and the α phase exists at temperatures below 600°C. In particular, referring to Figure 2b, it is found that TiCr2 precipitates at about 600-650°C during the phase transformation from the high-temperature β phase to the low-temperature α phase.

[0071] Meanwhile, referring to FIG. 2c, in the case of the titanium alloy specimen manufactured by adding 0.5 wt. % of ferrochromium, unlike FIG. 2b, it can be seen that almost no precipitates are formed.

[0072] 3a and 3b show the mechanical properties of the comparative samples 1 to 4 and the example samples 1 to 8.

[0073] The specimen according to Comparative Example 3 is a titanium alloy specimen prepared by adding 4 wt% ferrochromium to pure titanium (Ti-0.05O), and the specimen according to Comparative Example 4 is a titanium alloy specimen prepared by adding 4 wt% ferrochromium to pure titanium (Ti-0.39O).

[0074] The mechanical properties were obtained by carrying out tensile tests on each titanium alloy specimen at room temperature and at a deformation rate of 1.5 mm / min.

[0075] Table 6 shows the mechanical properties of Samples 1 to 2 of the Comparative Examples and Samples 1 to 8 of the Examples.

[0076] [Table 6]

[0077] 3a, 3b and Table 6, the pure titanium specimens according to Comparative Examples 1 and 2, which do not contain ferrochromium, have a tensile strength of 418 to 758 MPa and a yield strength of 352 to 672 MPa. In contrast, the titanium alloy specimens manufactured by adding 3.0 wt% or less of ferrochromium to pure titanium have a tensile strength of 540 to 1370 MPa and a yield strength of 460 to 1280 MPa. In other words, the titanium alloys manufactured by adding ferrochromium have higher strength than pure titanium. In particular, referring to Table 6, the specimens according to Examples 3 to 7 have a tensile strength of 861 to 1165 MPa and good elongation.

[0078] Table 7 shows the measurement results of the elongation ratio of the specimens according to Comparative Examples 1 to 4 and the specimens according to Examples 1 to 8 and the observation results of the occurrence of cracks.

[0079] [Table 7]

[0080] Referring to FIG. 3a, FIG. 3b and Table 7, when comparing Comparative Example 1, Examples 1 to 4 and Comparative Example 3, and when comparing Comparative Example 2, Examples 5 to 8 and Comparative Example 4, it is seen that the elongation rate tends to decrease by adding ferrochromium to the pure titanium specimens.

[0081] However, in the case of Comparative Examples 3 and 4, when 4.0 wt% ferrochromium was added to pure titanium containing an oxygen concentration of 0.05 to 0.39 wt%, the elongation ratio dropped sharply to 1.1 to 1.4, but in the case of Examples 1 to 8, when less than 4.0 wt%, more specifically, 3.0 wt% or less ferrochromium was added to pure titanium containing an oxygen concentration of 0.05 to 0.39 wt%, the elongation ratio did not drop sharply and the range of elongation ratio was expressed as 2.2 to 16.8%. That is, when Examples 1 to 4 are compared with Comparative Example 3, and when Examples 5 to 8 are compared with Comparative Example 4, it can be seen that the addition of less than 4 wt% ferrochromium does not bring about a sharp drop in the elongation ratio, but the addition of 4 wt% or more ferrochromium brings about a sharp drop in the elongation ratio.

[0082] Furthermore, comparing Examples 1 to 3 with Example 4, and Examples 5 to 7 with Example 8, it can be seen that the degree of decrease in elongation is greater when the amount of ferrochrome added is 3.0 wt% than when the amount of ferrochrome added is 0.5 to 2.0 wt%. Therefore, in consideration of strength and elongation, it can be said that the amount of ferrochrome added is most preferably 0.5 to 2.0 wt%.

[0083] Also, referring to Table 7, it can be seen that in the case of the titanium alloy specimen according to Comparative Example 4, cracks were generated, but in the cases of the titanium alloy specimens according to Examples 1 to 8, no cracks were generated.

[0084] Although the present invention has been described above with reference to the illustrative drawings, the present invention is not limited to the embodiments and drawings disclosed in this specification, and it is clear that various modifications can be made by those skilled in the art within the scope of the technical concept of the present invention. Furthermore, even if the effects of the configuration of the present invention are not explicitly described and explained while the embodiments of the present invention are described above, it is natural that the effects that can be predicted by the configuration should also be recognized.

Claims

1. (a) adding ferrochromium to pure titanium (Ti); (b) forming a titanium alloy base material by melting and cooling the resultant of step (a); (c) hot forming the titanium alloy base material; Including, The ferrochrome contains 20 to 35% by weight of iron (Fe), 1 to 4% by weight of silicon (Si), and 0.15% by weight or less of carbon (C), with the remainder being chromium (Cr) and unavoidable impurities; The ferrochromium is added in an amount of less than 4% by weight based on the total weight of the titanium alloy. A method for manufacturing high-strength titanium alloys.

2. The ferrochromium is added in an amount of 0.5 to 2% by weight based on the total weight of the titanium alloy. A method for producing the high strength titanium alloy according to claim 1.

3. The hot forming is performed at 800 to 850 ° C. with a forming rate of 90% or less. A method for producing the high strength titanium alloy according to claim 1.

4. The titanium alloy produced contains 0.1-3.0 wt% chromium (Cr), 0.1-1.0 wt% iron (Fe), 0.01-0.1 wt% silicon (Si), 0.4 wt% or less oxygen (O), the balance being titanium (Ti) and unavoidable impurities, and has a tensile strength of 861-1165 MPa. A method for producing the high strength titanium alloy according to claim 1.

5. The alloy contains 0.1-3.0 wt% chromium (Cr), 0.1-1.0 wt% iron (Fe), 0.01-0.1 wt% silicon (Si), and 0.4 wt% or less oxygen (O), but the chromium (Cr) content is greater than the iron (Fe) content, with the remainder being titanium (Ti) and unavoidable impurities, and has a tensile strength of 861-1165 MPa. High strength titanium alloy.

6. The chromium content is 1.7 to 4 times the iron content. The high strength titanium alloy according to claim 5.

7. The titanium alloy is characterized in that it has a molybdenum equivalent ([Mo]eq.) represented by the following formula 1 of 5 or less and a β transformation point of 840 to 930 ° C. The high strength titanium alloy according to claim 5. [Formula 1] [Mo]eq. = [Mo] + 0.2 [Ta] + 0.28 [Nb] + 0.4 [W] + 0.67 [V] + 1.25 [Cr] + 1.25 [Ni] + 1.7 [Mn] + 1.7 [Co] + 2.5 [Fe]

8. The titanium alloy has a yield strength of 460 to 1280 MPa and a Young's modulus of 95 to 105 GPa. The high strength titanium alloy according to claim 5.

Citation Information

Patent Citations

  • Low-cost titanium alloy and preparation method thereof

    CN103045905A

  • High strength titanium alloy casting product

    JP1999036029A

  • Titanium alloy excellent in strength and ductility at room temperature

    JP2012052178A

  • High-strength, high-ductility titanium alloy and process for preparing the same

    WO1996033292A1